An Epigenetic Signature for Within-Generational Plasticity of a Reef Fish to Ocean Warming - Ryu, Taewoo; Veilleux, Heather D.; Munday, Philip L.; Jung, Imgook; Donelson, Jennifer M.; Ravasi, Timothy (Frontiers in Marine Science, 2020)
Elevated temperature can have detrimental effects on the physiological performance of many marine organisms. However, phenotypic plasticity may enable some populations to maintain their performance under stressful conditions. Two populations of the coral reef fish, Acanthochromis polyacanthus from the Great Barrier Reef have shown differing capacities for thermal plasticity - the Heron Island population restored aerobic scope within one generation at a higher temperature, whereas the Palm Island population restored aerobic scope only when two generations were exposed to warmer conditions. We recently discovered an epigenetic signature associated with transgenerational plasticity in the Palm Island population. Here, we aimed to determine if epigenetic changes are also associated with the within-generational plasticity in the Heron Island population and, if so, how this epigenetic signature compares to the Palm Island transgenerational epigenome. By sequencing and analyzing the genome-wide DNA methylome of fish reared at control (+0 °C) or elevated temperatures (+1.5 and +3 °C) since early life, we identified 480 differentially methylated genomic regions and 372 adjacent protein-coding genes associated with within-generational plasticity in the Heron Island population. Functions related to insulin, cardiovascular capacity, development, and heat response were significantly enriched in differentially methylated genes, suggesting that these functions are the core mechanisms for within-generational restoration of aerobic scope. Comparison to the differentially methylated genes identified from F2 Palm Island population revealed little overlap of genes and enriched functions, indicating that distinct genetic toolkits may be used for within- and between-generational plasticity to ocean warming in the same species from different latitudes.